Hak Cipta Tari Pasuruan Kondhang dalam Perspektif Undang-Undang Republik Indonesia Nomor 28 Tahun 2014 (Studi di Lembaga Kursus dan Pelatihan Paguyuban Seni Tradisional Mustika Laras Kota Pasuruan) - Hikmah Amalia Putri Suyitno; Ronny Winarno Penulis; Yudhia Ismail (CV. ITTC INDONESIA, 2025)
Indonesia is a country rich in cultural diversity, including dance, music, traditions, and customs that have been passed down from generation to generation. This wealth is not only a national identity, but also has significant economic and social value. One of the unique cultural arts is the Pasuruan Kondhang Dance, which originates from Pasuruan City, East Java. This dance is not only a local symbol, but also contains historical and philosophical values that need to be protected and preserved. However, until now, the Pasuruan Kondhang Dance has not fully received legal protection according to applicable provisions. Legal protection for the copyright of traditional dance in Indonesia includes two types, namely preventive and repressive protection. This protection aims to maintain justice, in accordance with the mandate of Law of the Republic of Indonesia Number 28 of 2014 concerning Copyright. In its implementation, legal protection for the copyright of traditional dance not only provides recognition to the creator, but also provides security guarantees, both in the form of material and non-material. This study uses an empirical legal approach, namely a legal research method based on empirical facts obtained from human behavior, either through verbal interviews or direct observation. From the results of the study, it is known that legal protection for the Pasuruan Kondhang Dance in Pasuruan City is carried out through the process of inventory, security, and cultural promotion. The local government also seeks to protect this work from plagiarism, both by individuals and communities, with a normative approach based on laws and regulations. In addition, the government also took the initiative to register the Pasuruan Kondhang Dance as an Intangible Cultural Heritage. This study emphasizes the importance of synergy between legal regulations and public awareness to support the preservation of traditional arts and culture, both legally and socially.